Meningococcal Pneumonia in a Young Healthy Male - Abdullah M. Al Alawi (Case Reports in Infectious Diseases)
A 23-year-old male presented to the emergency department with one-day history of right-sided pleuritic chest pain, haemoptysis, and fever. In the emergency department, the blood pressure was 140/60 mmHg, heart rate 89/min, body temperature 40°C, respiratory rates 20 breaths/min, and oxygen saturation 98% in room air. Physical examination revealed rales and bronchial breathing in the right infrascapular region. Laboratory analysis showed raised white blood cell counts and elevated inflammation markers. Chest X-ray showed right lower lobe consolidation. Intravenous(IV) ceftriaxone and doxycycline were started for the management of community-acquired pneumonia as per the local guideline. Later, on admission, blood culture was positive for Neisseria meningitidis (N. meningitidis). Ceftriaxone was continued for 4 days, and the patient was discharged while being on oral amoxicillin (1 gm TDS) for another 3 days. He remained well during the outpatient follow-up.